A proposed model on the determinants of tax non-compliance behavior among small corporate taxpayers in Nigeria: The indirect effects of public governance quality and compliance cost - Musa, Sulaiman Umar; Saad, Natrah; Ibrahim, Idawati (2016)
In view of the declining oil prices and production challenges, Nigeria economy which is highly dependent on oil revenue must enhance its taxation to ensure stable flow of revenue for financing development.This study is a proposed model of small corporate taxpayers’ tax non-compliance behavior in Nigeria. This study reviews previous literature and developed its model based on deterrence and social exchange theories.This study extends the findings of previous studies by investigating the direct influence of the role of tax tribunal and the moderating and mediating effects of public governance quality and tax compliance costs respectively on non-compliance behavior of small corporate taxpayers in Nigeria. If the model is validated, this study would continue to collect data and analyze accordingly with the hope that the findings of the final study would help in formulating policy to curtailing tax non-compliance and hence increasing government revenue from taxation